Development of design thinking-based mathematics learning media to enhance mathematical critical thinking skills - Ariyani, Arneta Mayandha; Prayito, Muhammad; Happy, Nurina (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This research aims to develop an Android-based learning media application using MIT App Inventor to enhance students' mathematical critical thinking skills. The study employs a Research and Development (R&D) approach with the design thinking method, consisting of five stages: empathize, define, ideate, prototype, and test. During the empathize phase, in-depth interviews were conducted with five personas to identify existing issues, which were then summarized into an empathy map. In the define stage, data were analyzed using the How Might We technique to frame actionable problems. The ideate stage involved brainstorming solutions through mind mapping, followed by prototyping the application design based on the identified needs. In the testing phase, the application was evaluated for effectiveness (measured by success rate), efficiency (time-based metrics), and user satisfaction (via the System Usability Scale). Data were collected through questionnaires to assess the application’s viability, efficiency, and alignment with user needs. After completing the design thinking process, a critical thinking competency test was administered to compare learning outcomes on three-variable linear equations before and after using the media. Post-intervention results revealed above-average scores, demonstrating the application’s positive impact on students' mathematical critical thinking abilities. This study contributes to innovative learning media development in mathematics education, offering a simple, interactive, and accessible tool adaptable to individual learning needs.